Odpowiedzi

Najlepsza Odpowiedź!
2010-01-18T15:09:32+01:00
1) 2x+3=x-7
2x-x=7-3
x=4
2) 3(x-4)=5
3x-12=5
3x=5+12
3x=17/3
x=5 2/3
3) 3x+4(x-1)=5x-10
3x+4x-4=5x-10
3x-5x=-10+4
-2x=-6/(-2)
x=3
2 3 2
2010-01-18T15:13:20+01:00
1) 2x+3=x-7
2x-x = -7-3
x = -10

spr:
L= 2 * (-10) + 3 = -20 + 3 = -17
P= -10 - 7 = -17
P=L

2) 3(x-4)=5
3x-12= 5
3x= 5 +12/:3
x= 17:3
x= 5 i 2/3

3) 3x+4(x-1)=5x-10
3x + 4x- 4= 5x-10
7x- 5x = -10 +4
2x = -6/:2
x = -3
2010-01-18T15:15:04+01:00
1) 2x+3=x-7 |-x
x+3=-7 |-3
x=-10
2) 3(x-4)= 5
3x-12=5 |+12
3x=17 |/3
x=5+ 2/3
3) 3x+4(x-1)=5x-10
3x+4x-4=5x-10 |+4
7x=5x-6 |-5x
2x=-6 |/2
x=-3